2019
DOI: 10.1038/s41409-019-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of low-dose total body irradiation in HLA-mismatched reduced-intensity stem cell transplantation

Abstract: The significance of low-dose total body irradiation (TBI) in HLA-mismatched reduced-intensity conditioning stem cell transplantation (RICT) remains unknown. We, retrospectively, evaluated the impact of low-dose TBI in patients with hematological malignancies who received first RICT from ≥1 antigen-mismatched donors between 2004 and 2014. Of the 575 patients, 361 patients received low-dose TBI (2 or 4 Gy). There were no significant differences in neutrophil engraftment or platelet recovery between TBI and non-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Outcomes after HLA-mismatched donor HCT in the context of reduced-intensity conditioning have mainly been addressed in registry-based studies [14][15][16] ; observed ranges of grade 2 to 4 acute and chronic GVHD were similar to the current trial, but the incidence of grade 3 to 4 acute GVHD was higher, ranging from 13% to 27%, and resulting in NRM between 31.9% and 39% and overall survival rates between 30% and 48% at 3 years' posttransplantation. Parody et al 17 investigated the efficacy of sirolimus in combination with tacrolimus after reduced-intensity HCT in a prospective study in which a subpopulation of patients (n 5 20) was mismatched for a single HLA antigen.…”
Section: Discussionmentioning
confidence: 62%
“…Outcomes after HLA-mismatched donor HCT in the context of reduced-intensity conditioning have mainly been addressed in registry-based studies [14][15][16] ; observed ranges of grade 2 to 4 acute and chronic GVHD were similar to the current trial, but the incidence of grade 3 to 4 acute GVHD was higher, ranging from 13% to 27%, and resulting in NRM between 31.9% and 39% and overall survival rates between 30% and 48% at 3 years' posttransplantation. Parody et al 17 investigated the efficacy of sirolimus in combination with tacrolimus after reduced-intensity HCT in a prospective study in which a subpopulation of patients (n 5 20) was mismatched for a single HLA antigen.…”
Section: Discussionmentioning
confidence: 62%
“…40 However, a study of the clinical significance of low-dose TBI in patients with hematologic malignancies undergoing HSCT found that low-dose TBI improved OS in patients with a high-risk disease and multi-HLA mismatch in comparing to Flu/Bu conditioning. 41 It seems that TBI dosage could play a crucial role in post-transplant outcomes. On the other side, it is well accepted that low-dose TBI is less toxic.…”
Section: Therapeutic Advances In Hematologymentioning
confidence: 99%